Evaluation of a health promotion program in children: Study protocol and design of the cluster-randomized Baden-Württemberg primary school study [DRKS-ID: DRKS00000494] - Dreyhaupt Jens; Koch Benjamin; Wirt Tamara; Schreiber Anja; Brandstetter Susanne; Kesztyüs Dorothea; Wartha Olivia; Kobel Susanne; Kettner Sarah; Prokopchuk Dmytro; Hundsdörfer Verena; Klepsch Melina; et al. (BMC, 2012)
Abstract Background Increasing prevalences of overweight and obesity in children are known problems in industrialized countries. Early prevention is important as overweight and obesity persist over time and are related with health problems later in adulthood. "Komm mit in das gesunde Boot - Grundschule" is a school-based program to promote a healthier lifestyle. Main goals of the intervention are to increase physical activity, decrease the consumption of sugar-sweetened beverages, and to decrease time spent sedentary by promoting active choices for healthy lifestyle. The program to date is distributed by 34 project delivery consultants in the state of Baden-Württemberg and is currently implemented in 427 primary schools. The efficacy of this large scale intervention is examined via the Baden-Württemberg Study. Methods/Design The Baden-Württemberg Study is a prospective, stratified, cluster-randomized, and longitudinal study with two groups (intervention group and control group). Measurements were taken at the beginning of the academic years 2010/2011 and 2011/2012. Efficacy of the intervention is being assessed using three main outcomes: changes in waist circumference, skinfold thickness and 6 minutes run. Stratified cluster-randomization (according to class grade level) was performed for primary schools; pupils, teachers/principals, and parents were investigated. An approximately balanced number of classes in intervention group and control group could be reached by stratified randomization and was maintained at follow-up. Discussion At present, "Komm mit in das Gesunde Boot - Grundschule" is the largest school-based health promotion program in Germany. Comparative objective main outcomes are used for the evaluation of efficacy. Simulations showed sufficient power with the existing sample size. Therefore, the results will show whether the promotion of a healthier lifestyle in primary school children is possible using a relatively low effort within a school-based program involving children, teachers and parents. The research team anticipates that not only efficacy will be proven in this study but also expects many other positive effects of the program. Trial registration German Clinical Trials Register (DRKS), DRKS-ID: DRKS00000494